Survey, Analysis and Issues of Islamic Android Apps - Anum Hameed; Hafiza Anisa Ahmed; Narmeen Zakaria Bawany (Elkawnie: Journal of Islamic Science and Technology, 2019)
Mobile devices like Smartphones, tablets and PDAs have become an indispensable part of every person’s day to day activities. The growth and propagation of the smartphones has created new opportunities for religious app developers to develop apps that will provide utilities and an easy accessibility to religious information. The purpose of this research is to conduct a survey and to classify Islamic apps that are available on Google Play Store. The user surveys were conducted to evaluate and investigate the usage pattern of the Islamic apps in everyday life of the Muslims. The results identify the need of authentication of the app content that gives rise to many critical issues and myths. Also, it stresses the need for a “Religion” category in Google Play Store. The benefit of this research is twofold, as it focuses on identifying which app features Muslim users are more interested in using and secondly, the Islamic apps/features that need to be developed.